Modern collateral instruments and underlying assets for collateral: a sharīʿah compatibility analysis - Adawiah, Engku Rabiah; Mohd. Sulaiman, Aiman @ Nariman; Haron, Muhamad Nasir; Jaafar, Syaza Jamilah 'Inani (International Shari’ah Research Academy for Islamic Finance (ISRA), 2018)
Collateral or security is an integral part of the banking industry as it serves as a risk mitigation device. It is a common practice for banks and financial institutions to request security from their customers for financing facilities that will act as a “cushion” for the financial institutions in case of customer default. Like conventional banks, Islamic banks also require security under their financial arrangements. Most of the security instruments and the underlying assets used and accepted within the Islamic financing sphere mirror the conventional practices. This necessitates a discussion on the compatibility of these practices with the Sharīʿah. This research adopts a qualitative comparative study of the legal position of modern collateral instruments and the Sharīʿah position. From the legal perspective, the research is undertaken by way of doctrinal analysis of statutory provisions, relevant case law and a review of secondary sources in the form of books, journal articles and reports. The Sharīʿah position is established by a review of classical and contemporary writings, especially the juristic discourse on rahn and ʿuqūd altawthīqāt. The research also relies on a focus group discussion (FGD) conducted at the International Centre for Education in Islamic Finance (INCEIF) on 19 September 2017. Twenty-five participants comprising industry practitioners, experts, selected Sharīʿah scholars and legal advisors were asked to identify specific issues pertaining to collateral arrangements in the market from the practical, legal and Sharīʿah perspectives. The study finds that the most common form of security or collateral instrument used by banks for their corporate clients is the charge over corporate assets. The study also discovers that the Islamic security contract of rahn is the closest equivalent to the modern collateral instrument of charge. While a fixed charge has a lot of similarities with a traditional rahn contract and is generally capable of meeting rahn requirements, there is no exact comparable equivalent of a floating charge under the Sharīʿah. It is true that a floating charge does not fulfil the requirements of rahn as stipulated by the majority of jurists (Ḥanafīs, Shāfiʿīs and Ḥanbalīs). Nevertheless, the opinion of the Mālikī jurists (which is the view preferred by the researchers) can be applied to tolerate the features of a floating charge that include elements of uncertainty and jahālah in the underlying assets. This is because, since a security contract is supplemental in nature, the strict conditions of a primary sale contract should not be applied to a rahn contract. Further, making the conditions more flexible accords with the main objective of the rahn contract, which is to provide reassurance to the creditor regarding the debtor’s obligation in the event of failure to pay the debt. The changing nature of the assets subject to a floating charge also exposes the floating charge to the possibility that the assets may subsequently become Sharīʿah non-compliant. The research found that an asset that is Sharīʿah non-compliant in itself is not permissible for rahn purposes from the Sharīʿah perspective. However, there are assets that become Sharīʿah non-compliant due to external factors; for example, due to exterior elements such as ribā (interest) in conventional fixed deposits and bonds. This type of asset is permissible for rahn purposes provided that the ḥarām element is excluded. In addition, the common law accepts that some contractual arrangements, although not primarily created to secure debt obligations, may be used as security contracts. These are known as quasi-security arrangements and include debenture, contracts of indemnity or guarantee and assignments. Under Islamic law, the Islamic security contracts of kafālah/ḍamān and ḥawālah may be said to be comparable to, although not exactly the same as, some of the quasi-security contracts under common law such as contracts of indemnity or guarantee and assignments. Finally, the study analysed four types of ‘modern’ asset classes in term of their permissibility for use as the underlying asset in a rahn contract, apart from the traditionally accepted asset classes. These include shares, book debts, deposit accounts and intellectual property (IP). It is found, with regard to shares, that shares which are Sharīʿah non-compliant because the core business of the company is noncompliant cannot be used as collateral for Islamic financing. However, shares that are Sharīʿah noncompliant due to the contribution of Sharīʿah noncompliant activities that exceed certain benchmarks can be used as Islamic collateral, but only up to the ḥalāl portion, excluding the ḥarām portion. With regard to a charge over book debts, it is equivalent to a charge over receivables or rahn al-duyūn. Based on the Sharīʿah discussion on rahn al-duyūn, the researchers are of the view that book debts are permissible as collateral assets for rahn. This is because the registration of the book debts may be regarded as a form of constructive possession by the creditor, which would fulfil the rahn requirement. As for deposit accounts, the use of a conventional fixed deposit as collateral is allowed provided that such collateral is limited to the principal amount of the instrument only. Lastly, the use of IP as collateral or subject matter of rahn is possible as long as the security agreement is clear enough to contain all the information needed to ensure that the security transaction is valid.